Development strategy and macro-economic adjustment: (a perspective on inter-sectoral partnership and complementarity in policy and programme development) - Harris, Cary A. (Dominica Association for Industry & Commerce RoseauDM, 1993)
Identifies some basic principles relating to the private and public sectors with regard to their respective roles and how they may perceive the nature and scope of partnership.